2011
DOI: 10.1007/s00542-011-1259-1
|View full text |Cite
|
Sign up to set email alerts
|

Laser micro-structuring of magnetron-sputtered SnOx thin films as anode material for lithium ion batteries

Abstract: SnO x electrode thin films for lithium ion batteries were deposited by reactive and non-reactive rf magnetron sputtering of a SnO 2 target in an argon-oxygen atmosphere. Amorphous and nano-crystalline SnO x films could be synthesized, with regard to the O 2 :Ar volume ratio in the sputter gas which was adjusted to 0, 3.5 or 10%. Laser micro-structuring using a KrF excimer laser operating at a wavelength of k = 248 nm was applied to create free-standing microstructures. Thus, the active surface of the anode mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…All laser structuring experiments were carried out under ambient air without using any exhaust to allow the formation of self-organizing microstructures on the cathode material. The loss of active material by this type of laser structuring is limited to 0e10 wt% [5,9,10,26]. Laser-annealing of unstructured and laser structured thin films was performed in order to form HT-LCO using a high power diode laser (FLS IronScan, Fisba Optik AG) with a maximum laser power of 50 W operating at a wavelength of 940 nm.…”
Section: Preparation Of Electrodesmentioning
confidence: 99%
“…All laser structuring experiments were carried out under ambient air without using any exhaust to allow the formation of self-organizing microstructures on the cathode material. The loss of active material by this type of laser structuring is limited to 0e10 wt% [5,9,10,26]. Laser-annealing of unstructured and laser structured thin films was performed in order to form HT-LCO using a high power diode laser (FLS IronScan, Fisba Optik AG) with a maximum laser power of 50 W operating at a wavelength of 940 nm.…”
Section: Preparation Of Electrodesmentioning
confidence: 99%
“…A summary of 3D battery architectures is given in [12]. For this reason, excimer laser structuring of thin and thick film electrode materials was investigated in the past for increasing the active surface area by forming 3D microstructures directly into the active material [13][14][15][16][17]. Furthermore, conical microstructures could be formed in compact thin films as well as porous thick films [18].…”
Section: Introductionmentioning
confidence: 99%
“…A powerful technique to enhance the wetting properties of electrodes is laser patterning. Laser patterning processes have been developed for thin film electrode materials [4][5][6][7][8][9][10] as well as for thick tape-casted standard materials [11][12][13][14][15][16]. For the latter it could be shown that laser patterning of electrodes into three-dimensional (3D) micro-structures turns regular electrode surfaces into super-wicking accompanied with drastically increased electrolyte wetting speed [14][15][16].…”
Section: Introductionmentioning
confidence: 99%